Hammer head : the making of a carpenter - MacLaughlin, Nina (W.W. Norton & Company, 2015)
"Nina MacLaughlin spent her twenties working at a Boston newspaper, sitting behind a desk and staring at a screen. Yearning for more tangible work, she applied for a job she saw on Craigslist--'Carpenter's assistant : women strongly encouraged to apply'--despite being a Classics major who couldn't tell a Phillips from a flathead screwdriver. She got the job, and in [her book] she tells the ... story of becoming a carpenter"--Dust jacket flap.